In vitro survival of Bifidobacterium bifidum microencapsulated in zein-coated alginate hydrogel microbeads. (17th February 2019) - Riaz, Tahreem; Iqbal, Muhammad Waheed; Saeed, Muhammad; Yasmin, Iqra; Hassanin, Hinawi A. M.; Mahmood, Shahid; Rehman, Abdur
Abstract: The Bifidobacterium bifidum susceptibility in gastrointestinal conditions and storage stability limit its use as potential probiotics. The current study was design to encapsulate B. bifidum using sodium alginate (SA, 1.4% w/v) and different concentration of zein as coating material, that is, Z 1 (1% w/v), Z 2 (3% w/v), Z 3 (5% w/v), Z 4 (7% w/v), Z 5 (9% w/v). The resultant microbeads were further investigated for encapsulation efficiency, survival in gastrointestinal conditions, release profile in intestinal fluid, storage stability and morphological characteristics. The highest encapsulation efficiency (94.56%) and viable count (>10 7 log CFU/g) was observed in Z 4 (7% w/v). Viable cell count of B . bifidum was >10 6 log CFU/g in all the zein-coated microbeads as compare to free cells (10 3 log CFU/g) and SA (10 5 log CFU/g) at 4 °C after 32 days of storage. Therefore, B. bifidum encapsulated in zein-coated alginate microbeads present improved survival during gastric transit and storage.